SUSTAINABLE WASTEWATER TREATMENT FOR LBOD USING CONSTRUCTED WETLANDS - Sher Muhammad Ghoto; Irfan Kamboh; Muhammad Sajjad Zardari; Sajjad Bhangwar; Saira Akram Arain; Muhammad Ramzan Luhur (Spectrum of Engineering Sciences, 2025)
Pakistan is an agricultural and growing industrial country in the developing world. The large volume of wastewater is disposed of through drainage systems in natural water bodies without any primary treatment. Pakistan's largest drainage project has been prepared to control wastewater and waterlogging. The Left Bank Outfall Drain (LBOD) Drainage System faces severe problems. The country is experiencing demographic, economic, and energy crises that pose severe barriers to capital investment in the wastewater treatment program. It is due to the complexity of the process, high energy consumption, lack of highly trained operators, and high capital and operational costs that have made it difficult to adopt conventional treatment systems for treating the wastewater of this large water body. This study aims to provide sustainable, low-cost, energy-efficient wastewater treatment solutions. To accomplish this objective, the application of constructed wetlands for the treatment of wastewater (LBOD) has been investigated. This work may be considered a tool for researchers and decision-makers to design and manage the parameters of constructed wetlands to treat wastewater in particular areas, including macrophyte species, media types, water level, hydraulic retention time, and hydraulic load rate (HLR).